2008
DOI: 10.1200/jco.2008.16.3766
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Lymphedema in Women With Breast Cancer 5 Years After Sentinel Lymph Node Biopsy or Axillary Dissection: Patient Perceptions and Precautionary Behaviors

Abstract: A B S T R A C T PurposeSentinel lymph node (SLN) biopsy was adopted for the staging of the axilla with the assumption that it would reduce the risk of lymphedema in women with breast cancer. This study was undertaken to examine patient perceptions of lymphedema and use of precautionary behaviors several years after axillary surgery. Patients and MethodsNine hundred thirty-six women who underwent SLN biopsy (SLNB) alone or SLNB followed by axillary lymph node dissection (SLNB/ALND) between June 1, 1999, and May… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
115
0
8

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 196 publications
(130 citation statements)
references
References 28 publications
7
115
0
8
Order By: Relevance
“…17,29,30 It is reported that the lymphedema frequency, which is recommended to be performed in axilla-negative cases today compared to AD. [31][32][33][34][35][36][37][38] In our study, RT treatment seemed to be one of the major factors that increased the lymphedema incidence. In the literature, even cases without surgical intervention with RT to the axilla showed increased lymphedema incidence; moreover, with the combination of AD, it is reported to increase the lymphedema risk even more by showing a synergistic effect.…”
Section: Resultsmentioning
confidence: 94%
“…17,29,30 It is reported that the lymphedema frequency, which is recommended to be performed in axilla-negative cases today compared to AD. [31][32][33][34][35][36][37][38] In our study, RT treatment seemed to be one of the major factors that increased the lymphedema incidence. In the literature, even cases without surgical intervention with RT to the axilla showed increased lymphedema incidence; moreover, with the combination of AD, it is reported to increase the lymphedema risk even more by showing a synergistic effect.…”
Section: Resultsmentioning
confidence: 94%
“…Subjective symptom experience is the most important parameter for assessing physical function (Segerstrӧm et al 1991) and is often a major source of discomfort for patients (Petrek et al 2000). The more the patients perceive a certain symptom, the more likely they will behave to avoid that symptom (McLaughlin et al 2008). Our education program might have helped patients understand the symptoms related to breast surgery and made them check their symptoms in daily life.…”
Section: Discussionmentioning
confidence: 99%
“…The first author is a registered nurse and has been involved in education and research in breast nursing for more than 20 years. We used a pamphlet focusing on the etiology of upper arm dysfunction; the patients practiced the measurement of arm girth and assessment of 15 symptoms to identify changes in their arm; and they were also taught a risk minimization strategy (McLaughlin et al 2008) including a technique for lymphatic drainage of lymphedema and exercises for shoulder ROM. Telephone consultations were also provided.…”
Section: Interventionmentioning
confidence: 99%
“…AD, however, became an essential staging procedure enabling stratification of the patients to the appropriate adjuvant treatment. This procedure, however, also exposes 78% of early stage breast cancer patients to overtreatment with a 16% risk of lymphedema in five years [8]. With the appearance of the lymphatic mapping technique, three seminal studies, MILAN, NSABP-B32, and ALMANAC trials established sentinel lymph node biopsy (SLNB), a much less invasive procedure, as the new standard for staging of the axilla [9][10][11][12].…”
Section: Reviewmentioning
confidence: 99%
“…Although SLNB is a minimally invasive procedure it is still associated with some morbidity including a risk of lymphedema amounting to five percent at five years [8]. The SOUND trial at the European Institute of Oncology is investigating whether ultrasound staging of the axilla could substitute SLNB.…”
Section: Reviewmentioning
confidence: 99%